Role of NADPH oxidase in MAPK signaling activation by a 50 Hz magnetic field in human neuroblastoma cells. (2nd January 2021) - Martínez, María Antonia; Úbeda, Alejandro; Trillo, María Ángeles
ABSTRACT: Our previous studies have shown that intermittent exposure to a 50-Hz, 100-µT sine wave magnetic field (MF) promotes human NB69 cell proliferation, mediated by activation of the epidermal growth factor receptor (EGFR) and pathways MAPK-ERK1/2 and p38; being the effects on proliferation and p38 activation blocked by the chelator N-acetylcysteine. The present work investigates the MF effects on free radical (FR) production, and the potential involvement of NADPH oxidase, the main source of reactive oxygen species (ROS), in the MF-induced activation of MAPK pathways. To this end, the field effects on MAPK-ERK1/2, -p38 and -JNK activation in the presence or absence of the NADPH oxidase inhibitor, diphenyleneiodonium chloride (DPI), as well as the expression of the p67phox subunit, were analyzed. The results revealed that field exposure increases FR production and induces early, transient expression of the cytosolic component of the NADPH oxidase, p67phox. Also, the MF-induced activation of the MAPK-JNK pathway, but not that of -ERK1/2 or -p38 pathways, was prevented in the presence of the DPI, which has been shown to significantly reduce p67phox expression. These data, together with those from previous studies, identify various, FR-dependent or -independent mechanisms, involved in the MF-induced proliferative response mediated by MAPK signaling activation.